Damping Procedure for Mixed Control with Variable Coefficients of the Neighborhood Model - Shmyrin, A.M; Yartsev, A.G (International Journal of Engineering and Technology, 2018)
In the article, a bilinear neighborhood model of an installation for maintaining the optimum temperature of the polyol is considered. To determine the heat transfer coefficient, traditional mixed control and mixed control with variable coefficients were carried out. To improve the mixed control procedure with variable coefficients, damping is applied - imposing restrictions on the possible variation of the values of the variable coefficients. A comparison of the results of mixed controls with the results of determining the heat transfer coefficient with the help of thermotechnical calculation is made. The values of the deviations of the neighborhood model are presented for different variants of mixed control.